2007
DOI: 10.2134/jeq2006.0235
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Phosphorus Extractants for Phosphorus‐31 Nuclear Magnetic Resonance Analysis

Abstract: The influence of pre-extractant, extractant, and post-extractant on total extracted amounts of P and organic P compound groups measured with 31P nuclear magnetic resonance (31P-NMR) in lacustrine sediment was examined. The main extractants investigated were sodium hydroxide (NaOH) and sodium hydroxide ethylenediaminetetraacetic acid (NaOH-EDTA) with bicarbonate buffered dithionite (BD) or EDTA as pre-extractants. Post extractions were conducted using either NaOH or NaOH-EDTA, depending on the main extractant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Phosphorus-31 nuclear magnetic resonance spectroscopy requires large sample sizes and may be insensitive to polyP tightly associated with metal cations in solid granules. Moreover, alkaline extractions may incompletely extract and partly hydrolyze polyP (30,31). Assays based on enzymes of polyP metabolism (either exopolyphosphatase followed by orthophosphate [PO 4 3Ϫ ] determination [32,33] or polyP kinase followed by ATP measurement [34,35]) entail purifying polyP, but purification procedures suffer from low yields (36,37) and there is no commercial source for the necessary enzymes.…”
mentioning
confidence: 99%
“…Phosphorus-31 nuclear magnetic resonance spectroscopy requires large sample sizes and may be insensitive to polyP tightly associated with metal cations in solid granules. Moreover, alkaline extractions may incompletely extract and partly hydrolyze polyP (30,31). Assays based on enzymes of polyP metabolism (either exopolyphosphatase followed by orthophosphate [PO 4 3Ϫ ] determination [32,33] or polyP kinase followed by ATP measurement [34,35]) entail purifying polyP, but purification procedures suffer from low yields (36,37) and there is no commercial source for the necessary enzymes.…”
mentioning
confidence: 99%
“…To reduce interference of paramagnetic ions (Fe and Mn) in 31 P NMR measurements, 5% (v/v) bicarbonate-buffered dithionite (BD) solution (0.11 M NaHCO 3 + 0.11 M Na 2 S 2 O 4 ) was added to the concentrated extracts (Zheng et al, 2013). The BD solution can reduce Fe and Mn to states more ready to release adsorbed P compounds (Ahlgren et al, 2007). The extracts were then freeze-dried and re-dissolved in 0.5 mL of D 2 O and 0.2 mL of M NaOH.…”
Section: P Nmrmentioning
confidence: 99%
“…Cade-Menun and Preston [5] found that an aqueous solution containing both NaOH and EDTA extracted the greatest diversity of P forms and the largest percentage of total phosphorus in soil. Recently, it has been shown that a 0.25 M NaOH and 0.05 M EDTA extracting solution was most efficient in solubilizing a maximum range of organic P forms from sediments [26,28], while minimizing the co-extraction of Fe (III) and Mn (II) metals, which may significantly affect the resolution and intensity of 31 P NMR spectra [14,1]. Addition of HCl or Chelex to extracts was also found to be useful in reducing interferences [13,24].…”
mentioning
confidence: 99%